Current Aspects of the Role of Autoantibodies Directed Against Appetite-Regulating Hormones and the Gut Microbiome in Eating Disorders - Smitka, Kvido; Prochazkova, Petra; Roubalova, Radka; Dvorak, Jiri; Papezova, Hana; Hill, Martin; Pokorny, Jaroslav; Kittnar, Otomar; Bilej, Martin; Tlaskalova-Hogenova, Helena (Frontiers in Endocrinology, 2021)
The equilibrium and reciprocal actions among appetite-stimulating (orexigenic) and appetite-suppressing (anorexigenic) signals synthesized in the gut, brain, microbiome and adipose tissue (AT), seems to play a pivotal role in the regulation of food intake and feeding behavior, anxiety, and depression. A disregulation of mechanisms controlling the energy balance may result in eating disorders such as anorexia nervosa (AN) and bulimia nervosa (BN). AN is a psychiatric disease defined by chronic self-induced extreme dietary restriction leading to an extremely low body weight and adiposity. BN is defined as out-of-control binge eating, which is compensated by self-induced vomiting, fasting, or excessive exercise. Certain gut microbiota-related compounds, like bacterial chaperone protein Escherichia coli caseinolytic protease B (ClpB) and food-derived antigens were recently described to trigger the production of autoantibodies cross-reacting with appetite-regulating hormones and neurotransmitters. Gut microbiome may be a potential manipulator for AT and energy homeostasis. Thus, the regulation of appetite, emotion, mood, and nutritional status is also under the control of neuroimmunoendocrine mechanisms by secretion of autoantibodies directed against neuropeptides, neuroactive metabolites, and peptides. In AN and BN, altered cholinergic, dopaminergic, adrenergic, and serotonergic relays may lead to abnormal AT, gut, and brain hormone secretion. The present review summarizes updated knowledge regarding the gut dysbiosis, gut-barrier permeability, short-chain fatty acids (SCFA), fecal microbial transplantation (FMT), blood-brain barrier permeability, and autoantibodies within the ghrelin and melanocortin systems in eating disorders. We expect that the new knowledge may be used for the development of a novel preventive and therapeutic approach for treatment of AN and BN.